(untitled) (Research, Society and Development, 2022)
Introduction: Spinal Muscular Atrophy (SMA) is a rare disease caused by genetic alterations that affect cells known as neurons, which control the various muscles of the body. Objective: to point out which physiotherapeutic treatments are performed in children with Spinal Muscular Atrophy (SMA), according to the evidence of the scientific literature. Methodology: a systematic review of scientific materials published in indexed journals was carried out between 2013 and 2022, using the Latin American and Caribbean Health Literature databases (LILACS), Scientific Electronic Library Online (SCIELO), and Medical Literature Analysis and Retrieval System Online (MEDLINE), and CAPES Periodicals, highlighting what is most current on the topic of this discussion. Conclusion: It was found that physical therapy is essential and mandatory for children with SMA, both in the motor and respiratory aspects, in addition to being necessary, new studies that outline protocols and perform more reliable outcomes on the subject.